TEKNIK DATA MINING DALAM PENILAIAN PENGAJARAN GURU BERDASARKAN INDEKS KEPUASAN SISWA - Gerardo, Bob Gary; Saifullah, Saifullah; Irawan, Eka (STMIK Budi Darma, 2019)
Teacher performance evaluation is a process of analysis in order to produce good teaching. The process of evaluating the performance of teachers in Kartika Pematangsiantar Middle School has not been so detailed (detailed). With such detailed assessment, it is feared that there will be subjective judgments (based on personal interests), which can lead to social jealousy for teachers who do not receive achievements. In the assessment of teacher teaching students need data on teacher satisfaction. In collecting data using questionnaires and variables used in this study there were 4 namely discipline, quality of teaching, behavior, and social relations. This study aims to assist the School in improving teacher performance, especially in the way of teaching teachers based on student satisfaction using C4.5 Method.Keywords: Data Mining, Method C4.5, Kartika Middle School, Teacher Teaching Evaluation Based on Student Satisfaction Index